1963
DOI: 10.1149/1.2425708
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Oxidation of Metals, Nickel in Oxygen

Abstract: The oxidation of Mond nickel was studied between 1000 ~ and 1200~ at oxygen pressures from 6.5 x 10 -3 to 20.4 arm. The oxidation rate was controlled by diffusion through the oxide and had a gross activation energy of 50 _ 4 kcal/mole. Least squares straight line fitting over the entire pressure range indicated the rate was proportional to Po21/5. However, the rates above 1 arm appeared insensitive to pressure. On this basis, the measured rates below 1 atm more closely follow the PO21/4 dependence expected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…This coincides with some studies reported in the literature [14,15,18 21,26]. Nevertheless, other authors have described the formation of a protective dark layer [15,20,21,26]. Discrepancies could result from the different expo sure times used in these works.…”
Section: Discussionsupporting
confidence: 86%
“…This coincides with some studies reported in the literature [14,15,18 21,26]. Nevertheless, other authors have described the formation of a protective dark layer [15,20,21,26]. Discrepancies could result from the different expo sure times used in these works.…”
Section: Discussionsupporting
confidence: 86%
“…The studies on the chemical diffusion [19][20][21][29][30][31][32][33][34][35][36][37][38][39][40][41] and of the self diffusion of nickel [19,[41][42][43][44][45][46], performed mainly at higher oxygen pressures, indicate that the matter transport in Ni 1Àd O occurs generally via double ionized nickel vacancies. A similar conclusion could be obtained from the relation between the concentration of defects, the diffusion coefficients, and the parabolic rate constants of nickel oxidation [21,[47][48][49][50][51].…”
Section: Introductionsupporting
confidence: 69%
“…The effects of exposures of chromia forming alloys to low pressures have been reported in the literature [10][11][12][13], but very little information is available on the effect of high pressure. Work by Baur, Bartlett [14] on pure nickel found that the oxidation rate of nickel is insensitive to pressure above atmospheric pressure. However, on advanced alloys under CO2 atmospheres Pint, Brese [15] found a complex dependence on pressure in that alloys of similar composition to RR1000 showed a decrease in the gravimetric oxidation rate at 125 bar pressure compared with 1 bar pressure.…”
Section: Introductionmentioning
confidence: 99%